Amphoteric hyperbranched polymers with multistimuli-responsive behavior in the application of polymer flooding. Issue 107 (16th October 2015) - Pu, Wan-Fen; Liu, Rui; Li, Bin; Jin, Fa-Yang; Peng, Qin; Sun, Lin; Du, Dai-Jun; Yao, Feng-Sheng
Abstract : Amphoteric hyperbranched polymers (AMHPMs) that respond to shear rate, temperature, salt, and pH were synthesized using a water free radical polymerization technique. Abstract : Amphoteric hyperbranched polymers (AMHPMs) that respond to shear rate, temperature, salt, and pH were synthesized using a water free radical polymerization technique. The M w of this novel polymer is much lower than that of the conventional linear hydrophobically associative polymer (HAPAM). The hydrodynamic size could be effectively tuned by adjusting the terminal functional groups of the hyperbranched monomer. In the semidilute regime, multiple hydrodynamic subchains and effective intermolecular associations between neighboring branches of polymeric chains cooperatively govern the comprehensive characteristics of AMHPMs. Rheological measurements revealed the pseudodilatant behavior in the lower shear rate region, followed by the pseudoplastic behavior of AMHPMs. Moreover, the elasticity of AMHPM-2 played a dominant role and no G c is observed within the experimental frequency. Static experiments convincingly proved that the multiple subchains provided AMHPMs with a wider temperature-, salt- and pH-responsive region in comparison to that for HAPAM. Most importantly, the reversible hydrodynamic characteristic scale due to the mutual transformation from association to disassociation, and the excellent anti-mechanical degradation for AMHPMs in the simulative porous medium, further verified that this unique type of hyperbranched polymer is promising for the application of polymer flooding for enhanced oil recovery (EOR).